LOS EFECTOS DE LA ACETIL-CHOLINA Y DEL ION POTASIO SOBRE EL MUSCULO AURICULAR DEL MAMIFERO - ROSENBLUETH, ARTURO; GARCIA RAMOS, J (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
A prepn of auricular muscle with normal blood supply was obtained by crushing the base of the right auricular appendage By appropriate measures either a slow or a fast automatic rhythm could be established, although the prepn is not spontaneously activ
ARCH INST CARDIOL MEX
Keywords: EFECTOS, ACETIL-CHOLINA, ION, POTASIO, MUSCULO, AURICULAR, MAMIFERO; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA